Achieving and Sustaining Treatment Targets in Rheumatoid Arthritis: A Retrospective Cohort Analysis in Indonesia - Fauzia, Fara; Hidayat, Rudy; Kusumo Wibowo, Suryo Anggoro; Sumariyono, Sumariyono; Parlindungan, Faisal; Ariane, Anna; Damanik, Johanda; Araminta, Abirianty Priandani; Damaratri, Suci (Kesmas, 2026)
Achieving and sustaining low disease activity (LDA) and remission in rheumatoid arthritis (RA) remains challenging. This study examined the rates and predictors of LDA/remission and sustained LDA/remission in an Indonesian RA cohort. A retrospective study of newly diagnosed adult patients attending a rheumatology clinic in 2020-2021 was conducted. Patients were followed for 12 months to evaluate achievement of LDA/remission, defined as DAS28-ESR ≤3.2, and those meeting the target were observed for an additional 12 months to evaluate sustained LDA/remission. Cox regression was used to identify predictors of time to LDA/remission and loss of LDA/remission. Of 166 participants, 91 (54.8%) achieved LDA/remission, with a median time of 10 months. Among these, 39 (41.8%) maintained LDA/remission for 12 months. The median time to loss of LDA/remission was also 10 months. In multivariate analysis, no baseline variables (age, sex, rheumatoid factor (RF) positivity, disease activity, obesity, or disease duration) predicted achieving or sustaining LDA/remission. In this Indonesian cohort, over half of patients reached LDA/remission within 12 months. However, fewer than half sustained it over the following year, highlighting the need for ongoing monitoring and timely treatment adjustments, even after remission is achieved.